Sterilization of Zeolite Media to Increase Arbuscular Mycorrhizal Fungi Colonization in Corn and Sorghum Plants - Robifahmi, Nur; Hanani, Muftia; Bachtiar, Taufiq; Flatian, Anggi Nico; Citraresmini, Ania (Journal of Tropical Mycorrhiza, 2024)
Productivity of crops such as maize and sorghum is often constrained by low soil fertility, especially in terms of nutrient availability. Arbuscular Mycorrhiza Fungi (FMA) can improve nutrient absorption and support plant growth through a symbiotic relationship with plant roots. However, the success of FMA colonisation is strongly influenced by the quality of the growing medium, which is often contaminated with competing microorganisms that inhibit its effectiveness. To address this issue, this study aimed to evaluate the effect of sterilisation methods on the colonisation of FMA in maize and sorghum plants. The sterilisation methods tested were autoclaving and gamma radiation. This study used a completely randomised design with 8 treatment combinations and 5 replications. Zeolite media was sterilised using autoclaving and gamma radiation at a dose of 50 kGy. Results showed that sterilisation with gamma radiation produced a higher number of mycorrhiza spores and increased root colonisation in maize and sorghum compared to autoclaving. Gamma radiation applied to one sorghum seedling resulted in the highest spore count, while two seedlings in one pot reduced colonisation efficiency due to competition for nutrients. Gamma radiation was more effective in improving the quality of growing media and supporting mycorrhiza colonisation, ultimately enhancing overall plant growth and nutrient absorption.